1997
DOI: 10.1038/sj.onc.1201008
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of the murine protein tyrosine phosphatase PEST to the epidermal growth factor (EGF) receptor through a Src homology 3 (SH3) domain-mediated association with Grb2

Abstract: The involvement of murine protein tyrosine phosphatase-PEST (MPTP ± PEST) in signal transduction pathways is suggested by its ability to dephosphorylate phosphotyrosine residues, its interaction with the adaptor protein SHC and by the presence of ®ve proline-rich stretches in its non-catalytic carboxyl terminus. Proline-rich sequences have been identi®ed as binding sites for Src homology 3 (SH3) domains found in proteins associated with signal transduction events. The ability of these sequences to act as SH3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 31 publications
(40 reference statements)
2
35
0
Order By: Relevance
“…For example, GRB2 binds by a multisite interaction with tyrosine-phosphorylated LRP (RPTP-␣), and this interaction can also mediate the activation by GRB2 of signaling through the Sos pathway (30,31). In addition, GRB2 associates with SH2 domain-containing PTPases in a variety of cell types (32)(33)(34) as well as with PTP-PEST (35). These data suggest that GRB2 may have an important cellular role in the regulation of PTPase activities as well as their association with other signaling proteins with potentially important effects on substrate localization or complex formation that influences the rate of dephosphorylation of various PTPase substrates.…”
Section: Fig 4 Binding Of Sh2 Domain-containing Adaptor Proteins Tomentioning
confidence: 92%
“…For example, GRB2 binds by a multisite interaction with tyrosine-phosphorylated LRP (RPTP-␣), and this interaction can also mediate the activation by GRB2 of signaling through the Sos pathway (30,31). In addition, GRB2 associates with SH2 domain-containing PTPases in a variety of cell types (32)(33)(34) as well as with PTP-PEST (35). These data suggest that GRB2 may have an important cellular role in the regulation of PTPase activities as well as their association with other signaling proteins with potentially important effects on substrate localization or complex formation that influences the rate of dephosphorylation of various PTPase substrates.…”
Section: Fig 4 Binding Of Sh2 Domain-containing Adaptor Proteins Tomentioning
confidence: 92%
“…Candidate phosphatases include PTP1B and PTP-PEST, which have been shown to directly interact with and dephosphorylate Cas (50,51). Interestingly, PTP-PEST was recently demonstrated to become recruited to activated EGF receptor complexes (52). In one study, insulininduced tyrosine dephosphorylation of FAK and paxillin was found to be mediated by protein phosphatase SHP2 (Ref.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is currently being tested. 2 Tyrosine 344 of PSTPIP is found in a YASI motif. We tested several SH2 domains for their ability to bind phosphorylated PSTPIP and we found that the SH2 domains of c-Abl, and of the Src kinases c-Src and Fyn are capable of such a function in vitro.…”
Section: Fig 5 Binding Of the Cth Domain Of Ptp-pest To Pstpip Is Ementioning
confidence: 99%
“…Cas , Hef1/Cas-L, Sin/Efs, and Csk (2)(3)(4)(5). In addition, a novel and non-classical polyproline region in PTP-PEST has been implicated in the binding of paxillin and Hic-5 (6 -9).…”
mentioning
confidence: 99%